Pengaruh Latihan Squat Menggunakan Resistend Band Terhadap Kekuatan Tungkai Pada Tim Futsal Putri Universitas Muhammadiyah Palopo - Peprianti Pairi; A. Heri Riswanto; hajeni hajeni; Rachmat Hidayat (Journal of SPORT (Sport, Physical Education, Organization, Recreation, and Training), 2023)
This study aims to determine the effect of squat exercises using resistance bands on leg strength in the um.palopo futsal team.the method used in this study is a one group protest postest design experiment with a quantitative approach. Based on the results of data analysis that has been carried out, it is known that the number of research subjects amounted to 12 subjects. With an average pretest value of 228.92 and a postest value of 257.00. Std devitation pretest 9,643 and postest 10,207. Minimum pretest score 211 and postest 242 Maximum prestest 242 and postest 275. And the normality test that the pre-test and post-test data have a value of Ï (Sig.) 0.05, then the variables are normally distributed. Since the data is normally distributed, it can continue. Then a t test was carried out with the results obtained, namely sig, which is 0.000 0.05. This can be seen from the sig value of 0.000 0.05 which means that Ho is rejected. Thus, it can be concluded that there is a significant influence on training using resistance bands on the leg strength of the um.palopo futsal team. This squat exercise aims to increase leg strength in the um.palopo futsal team.